COMPARATIVE ANALYSIS OF HYDROTHERMAL HEAT PUMP INSTALLATIONS OF CLOSED AND OPEN TYPES WITH DIFFERENT SOURCES OF LOW-POTENTIAL ENERGY - Zurian, O.; Barilo, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article is devoted to a new direction of using the waters of the upper aquifers and open reservoirs for heat and cold supply of residential and public buildings and structures. The theoretical analysis of technologies of construction and features of use of natural accumulators of thermal energy in aquifers is carried out. The general schemes of construction of hydrothermal power systems of closed and open type are described. The hydrothermal experimental heat pump power system developed and constructed at the Institute of Renewable Energy of the National Academy of Sciences of Ukraine consisting of a heat pump and two wells with a depth of 49.5 m and 57.5 m, through which water is pumped or pumped from the aquifer, is presented. The geomorphological, geological and hydrogeological conditions of the study site are analyzed. The peculiarities of the formation of groundwater reserves of the productive horizon are described. Further directions of hydrogeological observations have been determined. The efficiency of the hydrothermal heat pump energy system of the open type is scientifically substantiated. Research methods are described. The characteristics of the measuring equipment and the software which was used for archiving and visualization of the data received in the course of carrying out research work are resulted. The results of experimental researches are presented. A comparative analysis of the efficiency and investment attractiveness of the hydrothermal system of open and closed type, where low-potential thermal energy of water is used as a renewable primary source of thermal energy for the operation of the heat pump was carried out. It is established that the use of renewable low-potential ground energy for the operation of geothermal energy systems is widely used in environmentally safe and economically attractive energy systems. However, the use of hydropower potential in hydrothermal energy systems is not widely used, despite the high technical and economic performance. It is proved that the existing hydrothermal systems are not always adapted to the operating conditions and location of the facility. There is no method of designing open-type hydrothermal systems, methods of conducting preliminary hydrogeological studies of the area planned for the installation of these systems and methods of calculating the parameters of the storage medium. The data obtained during the study are of great scientific and applied importance in the design of hydrothermal energy heat pump systems. In addition, there are prospects for further research into the possibility and effectiveness of using the aquifer as a natural heat accumulator to stabilize the generation of energy from renewable sources, regardless of climatic conditions and time of year.